The mediating role of professional identity in the relationship between emotional work and work engagement: A study with Portuguese police. - Graça, Andreia Carolina Gil (2022)
Dissertação de Mestrado em Psicologia do Trabalho, das Organizações e dos Recursos Humanos apresentada à Faculdade de Psicologia e de Ciências da Educação